IMPLEMENTASI KEMITRAAN KEHUTANAN ANTARA KELOMPOK TANI DENGAN BKPH RINJANI BARAT PELANGAN TASTURA (Studi Kasus : Gabungan Kelompok Tani Maju Lestari, Desa Pusuk Lestari, Kecamatan Batulayar, Kabupaten Lombok Barat) - Rahayu Prasetya Utami; Yulia Ratnaningsih (Universitas Pendidikan Mataram, 2018)
Land grabbing is one of the factors contributing to high rate of deforestation and forest degradation, thus it should involve the local community in its management. One of the government’s policies to improve community participation in forest management is forestry partnership. The purpose of this research is to explore the process of implementation of forestry partnership between farmer group and BKPH Rinjani Barat PelanganTastura as well as its supporting and constraining factors. The data was collected by interview. The data obtained were analyzed descriptively. The results demonstrate that the process of forestry partnership implementationis well performed. The supporting factors of forestry partnership between farmer group and BKPH Rinjani Barat PelanganTastura are high quality seedlings, cultivated area, advanced maintenance and firm support from farmer groups for forestry partnership program, absolute trust fromfarmer groups inforest manager and massive support from other related farmer groups. Meanwhile the constraining factors of forestry partnership between farmer groups and BKPHRinjani Barat PelanganTasturais low quality of human resources, internal problems of farmer group organization, lack of communication between government and farmer groups and low participation of farmer groups.